Protein Trafficking or Cell Signaling: A Dilemma for the Adaptor Protein TOM1 - Roach, Tiffany G.; Lång, Heljä K. M.; Xiong, Wen; Ryhänen, Samppa J.; Capelluto, Daniel G. S. (Frontiers in Cell and Developmental Biology, 2021)
Lysosomal degradation of ubiquitinated transmembrane protein receptors (cargo) relies on the function of Endosomal Sorting Complex Required for Transport (ESCRT) protein complexes. The ESCRT machinery is comprised of five unique oligomeric complexes with distinct functions. Target of Myb1 (TOM1) is an ESCRT protein involved in the initial steps of endosomal cargo sorting. To exert its function, TOM1 associates with ubiquitin moieties on the cargo via its VHS and GAT domains. Several ESCRT proteins, including TOLLIP, Endofin, and Hrs, have been reported to form a complex with TOM1 at early endosomal membrane surfaces, which may potentiate the role of TOM1 in cargo sorting. More recently, it was found that TOM1 is involved in other physiological processes, including autophagy, immune responses, and neuroinflammation, which crosstalk with its endosomal cargo sorting function. Alteration of TOM1 function has emerged as a phosphoinositide-dependent survival mechanism for bacterial infections and cancer progression. Based on current knowledge of TOM1-dependent cellular processes, this review illustrates how TOM1 functions in coordination with an array of protein partners under physiological and pathological scenarios.